What sub-Saharan African countries can learn from malaria elimination in China - Abubakar Olaitan Badmos; Aishat Jumoke Alaran; Yusuff Adebayo Adebisi; Oumnia Bouaddi; Zainab Onibon; Adeniyi Dada; Xu Lin; Don Eliseo Lucero-Prisno (Tropical Medicine and Health, 2021)
Abstract Malaria is one of the most devastating diseases plaguing the sub-Saharan African region since time immemorial. In spite of a global reduction in mortality rates, a significant proportion of deaths due to malaria is still accounted for in the region. China recently joined the 40 countries declared malaria free by the World Health Organization and became the first country in the WHO Western Pacific Region to be awarded the certification. We commented on the strategies employed by China to eliminate malaria, address challenges facing malaria control in sub-Saharan Africa, and derive lessons that could be learned in the sub-Saharan African context.